Prospective changes in anemia are associated with the incidence and persistence of sarcopenia among older Mexican adults - De La Cruz-Góngora, Vanessa; Salinas-Rodriguez, Aaron; Manrique-Espinoza, Betty (Frontiers in Nutrition, 2024)
Background Low hemoglobin levels are a significant biomarker in the prognosis of sarcopenia. Anemia and sarcopenia are frequent and disabling conditions in the older adult population, but little is known about the role of anemia in the onset and progression of sarcopenia. This study aimed to determine whether prospective changes in anemia are associated with the incidence and persistence of sarcopenia. Methods Data come from the second and third waves (2014, 2017) of the World Health Organization (WHO) Study on global AGEing and adult health (SAGE) in Mexico. SAGE-Mexico is a dynamic cohort with national representativeness, including a follow-up sample and new enrollments. For this study, 1,500 older adults (aged 50 or above) with measurements in both waves were included. Sarcopenia was defined as having low muscle quantity and either/both slow gait speed and weak handgrip strength. Anemia was defined according to hemoglobin concentrations, adjusted for altitude, as recommended by the WHO, <120 g/L for women and <130 g/L for men. Multinomial logistic regression was used to estimate the association between anemia and prospective changes in sarcopenia. Results The baseline prevalence of anemia was 17.4%, and that of sarcopenia was 12.1%. The incidence and persistence of anemia were 10.6% (95% CI: 7.3–15.0%) and 6.9% (95% CI: 4.7–9.8%), respectively, and for sarcopenia, they were 5.3% (95% CI: 3.7–7.7%) and 9.2% (95% CI: 6.4–13.0%), respectively. Incident anemia was associated with incident (RRR = 3.64, 95% CI: 1.18–11.19) but not with persistent (RRR = 0.75, 95% CI: 0.18–3.20) sarcopenia. Persistent anemia was significantly associated with persistent (RRR = 3.59, 95% CI: 1.14–11.27) but not incident (RRR = 1.17, 95% CI: 0.30–4.54) sarcopenia. Conclusion Changes in anemia are significantly associated with incident and persistent sarcopenia. Primary actions to promote a healthy diet rich in antioxidants, high-quality proteins, and micronutrients, as well as moderate physical activity and maintaining a healthy weight, are crucial for the aging population to delay the deleterious effects of anemia and sarcopenia.